EFFECTS OF TYPE OF PHOSPHATE ADSORBENT COMPOUND AND SOURCE OF P FERTILIZER ON PHOSPHATE SUPPLYING CAPACITY OF PEAT MATERIAL - MASGANTI, .; NOTOHADIKUSUMO, T.; MAAS, A.; RADJAGUKGUK, B. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2003)
Peat soil has a negative charge through its functional groups such as carboxylic. On other side, phosphate is essential nutrient available in the form of anion, that the P becomes easily carried by leaching water. The use of P adsorbent compound could strengthen the bound between P anion and peat colloid, so the loss of P can be reduced. Besides that, the use of slow released P fertilizer containing adsorbent cations can also reduce the total P in the leachate. A laboratory experiment was conducted to determine kinds of adsorbent compound and source of P fertilizer which effectively increase P retention and P supplying capacity of sapric peat material from Berengbengkel, Palangkaraya, Central Kalimantan. The experiment was carried out in the Soil Laboratory, Gadjah Mada University, Yogyakarta from September until November 2001. The treatment factorsimposed were (1) kinds of adsorbent compound : CaCO3; CaSO4; CaCl2; MgCO3; MgSO4; MgCl2; K2CO3; K2SO4; KCl; Na2CO3; Na2SO4; NaCl; (NH4)2CO3; (NH4)2SO4; and NH4 Cl, and (2) source of P fertilizer: SP-36 and rock phosphate. The experiment was arranged in a randomized complete design with three replications. One hundred grams of moist sapric peat material (containing about 100% water) was mixed with adsorbent compound and 30 ?g g-1 P fertilizer, and incubated for one week. For five consecutive weeks, the peat was leached with 200 ml waterevery week. The parameters observed were P retention and supplying capacity of the peat. The results showed that P retention and P supplying capacity of the peat material were strongly affected by kinds of adsorbent compound, source of P fertilizer, and interaction of both. The P retention and P supplying capacity of the peat became maximum if using CaCO3 as an adsorbent compound and rock phosphate as a source of Pfertilizer.